Monitoring of Nutrient Spatial Dynamics for Sustainable Production of Coffee in São Paulo/Brazil - Zanguettin, Gustavo Bonacina; Ferraz Almeida, Risely (Directorate of Research and Community Services, 2025)
Brazil is considered the world's largest producer of coffee, requiring a large quantity of nutrients (i.e., potassium, nitrogen, phosphorus, calcium, magnesium, and others). The study monitored the spatial variability of nutrients in soil cultivated with Coffee in the region of Pompeia, São Paulo, Brazil. A grid was created with a layout of forty georeferenced points spaced 50 m apart. Soil samples were collected to determine their nutrient content. Results showed that the spatial variability of phosphorus and potassium was separated between the coffee planted in 2006 and 2017. The acidity was influenced by the nutrient contents. There was a uniform spatial variability of calcium and magnesium due to the similar application of liming. Based on the results, we conclude that in this case study, the use of spatial variability was a great alternative to monitor the spatial dynamics of nutrients. The time of planting was classified as the main factor that influences the spatial dynamics of soil nutrient contents.